Identification of Quantitative Proteomic Differences between Mycobacterium tuberculosis Lineages with Altered Virulence - Peters, Julian S.; Calder, Bridget; Gonnelli, Giulia; Degroeve, Sven; Rajaonarifara, Elinambinina; Mulder, Nicola; Soares, Nelson C.; Martens, Lennart; Blackburn, Jonathan M. (Frontiers in Microbiology, 2016)
Evidence currently suggests that as a species Mycobacterium tuberculosis exhibits very little genomic sequence diversity. Despite limited genetic variability, members of the Mycobacterium tuberculosis complex (MTBC) have been shown to exhibit vast discrepancies in phenotypic presentation in terms of virulence, elicited immune response and transmissibility. Here, we used qualitative and quantitative mass spectrometry tools to investigate the proteomes of seven clinically-relevant mycobacterial strains – four M. tuberculosis strains, M. bovis, M. bovis BCG and M. avium - that show varying degrees of pathogenicity and virulence, in an effort to rationalize the observed phenotypic differences. Following protein preparation, liquid chromatography mass spectrometry (LC MS/MS) and data capture were carried out using an LTQ Orbitrap Velos. Data analysis was carried out using a novel bioinformatics strategy, which yielded high protein coverage and was based on high confidence peptides. Through this approach, we directly identified a total of 3,788 unique M. tuberculosis proteins out of a theoretical proteome of 4,023 proteins and identified an average of 3,290 unique proteins for each of the MTBC organisms (representing 82% of the theoretical proteomes), as well as 4,250 unique M. avium proteins (80% of the theoretical proteome). Data analysis showed that all major classes of proteins are represented in every strain, but that there are significant quantitative differences between strains. Targeted selected reaction monitoring (SRM) assays were used to quantify the observed differential expression of a subset of 23 proteins identified by comparison to gene expression data as being of particular relevance to virulence. This analysis revealed differences in relative protein abundance between strains for proteins which may promote bacterial fitness in the more virulent W. Beijing strain. These differences may contribute to this strains’ capacity for surviving within the host and resisting treatment, which has contributed to its rapid spread. Through this approach, we have begun to describe the proteomic portrait of a successful mycobacterial pathogen.